Pharmaceutical industry funding of events for healthcare professionals on non-vitamin K oral anticoagulants in Australia: an observational study. Issue 8 (20th August 2019) - Behdarvand, Behrad; Karanges, Emily A; Bero, Lisa
Abstract : Objectives: To describe the nature, frequency and content of non-vitamin K oral anticoagulant (NOAC)-related events for healthcare professionals sponsored by the manufacturers of the NOACs in Australia. A secondary objective is to compare these data to the rate of dispensing of the NOACs in Australia. Design and setting: This cross-sectional study examined consolidated data from publicly available Australian pharmaceutical industry transparency reports from October 2011 to September 2015 on NOAC-related educational events. Data from April 2011 to June 2016 on NOAC dispensing, subsidised under Australia's Pharmaceutical Benefits Scheme (PBS), were obtained from the Department of Health and the Department of Human Services. Main outcome measures: Characteristics of NOAC-related educational events including costs (in Australian dollars, $A), numbers of events, information on healthcare professional attendees and content of events; and NOAC dispensing rates. Results: During the study period, there were 2797 NOAC-related events, costing manufacturers a total of $A10 578 745. Total expenditure for meals and beverages at all events was $A4 238 962. Events were predominantly attended by general practitioners (42%, 1174/2797), cardiologists (35%, 977/2797) and haematologists (23%, 635/2797). About 48% (1347/2797) of events were held in non-clinical settings, mainly restaurants, bars and cafes. Around 55% (1551/2797) of events consisted of either conferences, meetings or seminars. The analysis of the content presented at two events detected promotion of NOACs for unapproved indications, an emphasis on a favourable benefit/harm profile, and that all speakers had close ties with the manufacturers of the NOACs. Following PBS listings relevant to each NOAC, the numbers of events related to that NOAC and the prescribing of that NOAC increased. Conclusions: Our findings suggest that the substantial investment in NOAC-related events made by four pharmaceutical companies had a promotional purpose. Healthcare professionals should seek independent information on newly subsidised medicines from, for example, government agencies or drug bulletins.